2018
DOI: 10.1097/pcc.0000000000001484
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Adsorption of Analgosedative Drugs in New Extracorporeal Membrane Oxygenation Circuits

Abstract: Loss of highly lipophilic drugs in the extracorporeal membrane oxygenation circuits at 24 hours was remarkable. Drug loss is comparable with other hollow fiber extracorporeal membrane oxygenation systems but less than in silicone-based membranes especially in the first hours after injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 37 publications
1
38
1
Order By: Relevance
“…[2][3][4][5][6][7] In the authors' institution, multiple experiments have been performed to determine in vitro drug recovery in extracorporeal membrane oxygenation (ECMO) systems. 8,9 Drug recovery has been defined as the concentration of drug present in the priming fluid after a certain amount of time has passed since addition of the drug to the CPB system. 8,9 Previous publications have used the term absorption to indicate the decrease in concentration of drug in the priming fluid.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7] In the authors' institution, multiple experiments have been performed to determine in vitro drug recovery in extracorporeal membrane oxygenation (ECMO) systems. 8,9 Drug recovery has been defined as the concentration of drug present in the priming fluid after a certain amount of time has passed since addition of the drug to the CPB system. 8,9 Previous publications have used the term absorption to indicate the decrease in concentration of drug in the priming fluid.…”
mentioning
confidence: 99%
“…Sequestration in these systems is expected for lipophilic drugs, such as sufentanil or midazolam. 13 As shown by Shekar et al 14 in ECMO circuits, drugs with a LogP greater than 2.3 have a significantly higher decrease in the concentration compared to less lipophilic or hydrophilic drugs. As both cefazolin and clindamycin have a lower LogP they are not expected to sequester in the CPB systems (see Table 5).…”
Section: Discussionmentioning
confidence: 93%
“…Hydrophilic drugs such as clindamycin are not known to sequester in CPB systems. Sequestration in these systems is expected for lipophilic drugs, such as sufentanil or midazolam . As shown by Shekar et al in ECMO circuits, drugs with a LogP greater than 2.3 have a significantly higher decrease in the concentration compared to less lipophilic or hydrophilic drugs.…”
Section: Discussionmentioning
confidence: 97%
“…However, in vitro data reported that mechanisms behind changed CL are not clear yet -it depends on drug lipophilicity, but also on the bindingsite saturation. [5][6][7][8] Phenobarbital, phenytoin and fos-phenytoin are anticonvulsive drugs used in neonates and infants undergoing ECMO to treat seizures (18-20%) and withdrawal symptoms. [8][9][10] There is insufficient data on the potential impact of ECMO on the PK of phenobarbital.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Phenobarbital, phenytoin and fos-phenytoin are anticonvulsive drugs used in neonates and infants undergoing ECMO to treat seizures (18-20%) and withdrawal symptoms. [8][9][10] There is insufficient data on the potential impact of ECMO on the PK of phenobarbital. 11 A number of publications reported serum concentrations of phenobarbital after the loading dose (LD) to be decreased (24 hours) due to the large Vd, while concentrations measured during the maintenance dose (MD) regimen were still within the therapeutic range and the calculated t 1/2 was similar to neonates receiving phenobarbital without ECMO.…”
Section: Introductionmentioning
confidence: 99%